2010
DOI: 10.2106/jbjs.i.00749
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Obesity on Femoral Osteolysis Five and Ten Years Following Total Hip Arthroplasty

Abstract: Prognostic Level I. See Instructions to Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 36 publications
1
14
0
1
Order By: Relevance
“…Clinical evidence of the effect of BMI on revision rates is mixed. Some clinical studies have shown that BMI correlated with revision risk (Münger et al, 2006; Röder et al, 2008) others that it did not (Lübbeke et al, 2010). Ideally, we would have included donor activity level as an additional predictor but the data were not available.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical evidence of the effect of BMI on revision rates is mixed. Some clinical studies have shown that BMI correlated with revision risk (Münger et al, 2006; Röder et al, 2008) others that it did not (Lübbeke et al, 2010). Ideally, we would have included donor activity level as an additional predictor but the data were not available.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Workgroup of the American Association of Hip and Knee Surgeons Evidence-Based Committee determined from their literature review that all obese patients (ie, BMI .30) appear to be at risk for an increasing number of perioperative complications after total joint arthroplasty (TJA), especially with poorly controlled comorbidities. 27 Implant survival times also are similar, 28 although some clinicians reported significantly lower implant survival times in morbidly obese patients and more technical errors in obese patients. Dislocation also occurs more frequently after THA in obese patients.…”
Section: Total Joint Knee and Hip Arthroplastymentioning
confidence: 94%
“…Obesity is associated with a higher incidence of perioperative complications including cardiovascular and respiratory events 42 , venous thrombosis 43 , wound infection 44 , and dislocation 45 . However, despite the increase in joint load in these patients, no consistent increase in bearing wear or osteolysis has been shown across study populations 46,47 and thus obesity is not a clear risk factor for osteolysis.…”
Section: Body Mass Index and Obesitymentioning
confidence: 68%